Religiosity and quality of life in older adults: literature review - Abdala, Gina Andrade; Kimura, Miako; Koenig, Harold G.; Reinert, Katia G.; Horton, Khim (Journal of Interdisciplinary Lifestyle Studies, 2016)
Older adults are living longer, often with one or more long-term health conditions which can impact their quality of life. In fact, a growing number of studies have shown a positive association between religion/spirituality and better quality of life for older adults. The aim of this paper is To examine the association between religiosity/spirituality and quality of life among older adults. In order to accomplish this objective, an integrative literature review will be made in which the following eletronic databases were searched: Lilacs, Scielo, Medline, and Pubmed (see keywords below). The inclusion criteria were: studies written in English, Portuguese or Spanish, published between 2004 and 2012, containing themes pertaining to the research question as noted above, and having full texts freely available. The exclusion criteria were literature reviews and participants under 60 years of age. Only 12 studies met the inclusion criteria. All reviewed researches had a cross-sectional design. In 75% of the studies, a positive association between religion/ spirituality and quality of life was found. Three studies reported no association. Greater religious/spiritual involvement was associated with better quality of life among older adults, who reported increased life satisfaction, less depressive symptoms and pain, better cognitive function and increased general and/or health-related quality of life. Religiosidade e qualidade de vida e pessoas com idade avançada: revisão de literatura. Pessoas com idade avançada estão vivendo mais, muitas vezes com mais condições de saúde a longo prazo, o que pode afetar sua qualidade de vida. Na verdade, um número crescente de estudos têm mostrado uma associação positiva entre a religião/espiritualidade e a melhor qualidade de vida para adultos. O objetivo deste trabalho é examinar a associação entre religiosidade/espiritualidade e qualidade de vida entre pessoas com idade avançada. A fim de alcançar este objectivo, uma revisão integrativa da literatura será feita na qual serão pesquisadas as seguintes bases de dados eletrônicas: Lilacs, Scielo, Medline e Pubmed (veja as palavras-chave abaixo). Os critérios de inclusão foram: estudos escritos em Português, Inglês ou Espanhol, publicado entre 2004 e 2012, contendo temas pertinentes à questão de pesquisa como mencionado acima, e tendo textos completos disponíveis gratuitamente. Os critérios de exclusão foram revisões de literatura e participantes com menos de 60 anos de idade. Apenas 12 estudos preencheram os critérios de inclusão. Todas as pesquisas de avaliação tiveram um aspecto transversal. Em 75% dos estudos, uma associação positiva entre a religião/espiritualidade e qualidade de vida foi encontrado. Três estudos não relataram nenhuma associação. Um maior envolvimento religioso/espiritual foi associado com melhor qualidade de vida entre pessoas de idade avançada, que relataram maior satisfação de vida, menos sintomas depressivos, menos dor, melhor função cognitiva e aumento da qualidade geral e/ou relacionada com a saúde.